Penentuan Lokasi Prioritas untuk Pengembangan Pelabuhan Perintis Menggunakan Metode Analytical Hierarchy Process - Martono, Ricky Virona (Journal of Emerging Business Management and Entrepreneurship Studies, 2024)
This article discusses the application of the Analytical Hierarchy Process (AHP) method by considering the weight of criteria to determine the best location alternative for pioneer port development in Indonesia. The criteria for choosing the best alternative of ports is based on Government Regulation number 61 / 2009; they are Availability of Port Facilities, Distance to Regional Port, and Economic Growth. The first step is to rank the criteria for all port alternatives based on each port’s current condition. These criteria are given weight relative to each other. This weighting benefits from prioritizing the location of pioneer ports based on the investor's point of view. Priority scores are given based on a comparison of qualitative data for each port, and then they are calculated in the Adjusted Matrix. The results determine the priority location of pioneer ports to be developed first because they are considered to provide the best benefits for development and for investors. On the other hand, other alternative locations that are not a priority do not mean they are rejected for development. To validate the consistency in giving scores, the consistency ratio was calculated, which score is less than one. The result of this article is to give the most priority to Kalimantan Tengah Port, followed by Nusa Tenggara Barat Port and Bangka Belitung Port.